Three-Color Imaging Using Fluorescent Proteins in Living Zebrafish Embryos. (July 2001) - Finley, Kenneth R.; Davidson, Ann E.; Ekker, Stephen C.
The zebrafish embryo is especially valuable for cell biological studies because of its optical clarity. In this system, use of an in vivo fluorescent reporter has been limited to green fluorescent protein (GFP). We have examined other fluorescent proteins alone or in conjunction with GFP to investigate their efficacy as markers for multi-labeling purposes in live zebrafish. By injecting plasmid DNA containing fluorescent protein expression cassettes, we generated single-, double-, or triple-labeled embryos using GFP, blue fluorescent protein (BFP, a color-shifted GFP), and red fluorescent protein (DsRed, a wild-type protein structurally related to GFP). Fluorescent imaging demonstrates that GFP and DsRed are highly stable proteins, exhibiting no detectable photoinstability, and a high signal-to-noise ratio. BFP demonstrated detectable photoinstability and a lower signal-to-noise ratio than either GFP or DsRed. Using appropriate filter sets, these fluorescent proteins can be independently detected even when simultaneously expressed in the same cells. Multiple labels in individual zebrafish cells open the door to a number of biological avenues of investigation, including multiple, independent tags of transgenic fish lines, lineage studies of wild-type proteins expressed using polycistronic messages, and the detection of protein-protein interactions at the subcellular level using fluorescent protein fusions.